William Forsythe - Choreographic objects - Neri, Louise; Respini, Eva 1976-; Birnbaum, Daniel 1963-; Forsythe, William 1949-; Foster, Susan Leigh 1949-; Groves, Rebecca M.; Nesbit, Molly 1952-; Sulcas, Roslyn (The Institute of Contemporary Art, 2018)
"What else, besides the body, could physical thinking look like? Choreographer William Forsythe asks this paradigmatic question in William Forsythe: Choreographic Objects, the first extensive publication dedicated to his provocative career in the intersecting disciplines of choreography, dance, and the visual arts. Published on the occasion of Forsythe's major exhibition at The Institute of Contemporary Art/ Boston, this landmark volume provides the first-ever comprehensive survey of the Choreographic Objects, a remarkable body of conceptual work that blurs the lines between performance, installation, sculpture, and video. Additionally, the richly illustrated volume offers illuminating context with original contributions from leading scholars and critics in the fields of the visual arts, choreography, and performance, together with an illustrated chronology of Forsythe's related dance repertoire"--
This book is published on the occasion of the exhibition "William Forsythe: Choreographic Objects", organized by Eva Respini, Barbara Lee, Chief Curator, with Jeffrey De Blois, Assistant Curator; The Institute of Contemporary Art/Boston, 31 October 2018-24 February 2019
Keywords: Forsythe, William -- 1949-; Choreografie; Forsythe, William / 1949- / Choreographic objects / Exhibitions; Interactive art / United States / Exhibitions; ART / Individual Artists / Monographs; ART / Conceptual; ART / Performance; Interactive art; United States; Exhibition catalogs; Ausstellungskatalog -- Institute of Contemporary Art -- 31.10.2018-24.02.2019 -- Boston, Mass.; Bildband